Practical use of dabigatran etexilate for stroke prevention in atrial fibrillation. Issue 6 (5th April 2013) - Huber, K.; Connolly, S. J.; Kher, A.; Christory, F.; Dan, G.‐A.; Hatala, R.; Kiss, R. G.; Meier, B.; Merkely, B.; Pieske, B.; Potpara, T.; Stępińska, J.; et al.
Summary Atrial fibrillation (AF) is associated with an increased risk of thromboembolism, and is the most prevalent factor for cardioembolic stroke. Vitamin K antagonists (VKAs) have been the standard of care for stroke prevention in patients with AF since the early 1990s. They are very effective for the prevention of cardioembolic stroke, but are limited by factors such as drug–drug interactions, food interactions, slow onset and offset of action, haemorrhage and need for routine anticoagulation monitoring to maintain a therapeutic international normalised ratio (INR). Multiple new oral anticoagulants have been developed as potential replacements for VKAs for stroke prevention in AF. Most are small synthetic molecules that target thrombin (e.g. dabigatran etexilate) or factor Xa (e.g. rivaroxaban, apixaban, edoxaban, betrixaban, YM150). These drugs have predictable pharmacokinetics that allow fixed dosing without routine laboratory monitoring. Dabigatran etexilate, the first of these new oral anticoagulants to be approved by the United States Food and Drug Administration and the European Medicines Agency for stroke prevention in patients with non‐valvular AF, represents an effective and safe alternative to VKAs. Under the auspices of the Regional Anticoagulation Working Group, a multidisciplinary group of experts in thrombosis and haemostasis from Central and Eastern Europe, an expert panel with expertise in AF convened to discuss practical, clinically important issues related to the long‐term use of dabigatran for stroke prevention in non‐valvular AF. The practical information reviewed in this article will help clinicians make appropriate use of this new therapeutic option in daily clinical practice.